1991
DOI: 10.1111/j.1365-3083.1991.tb01541.x
|View full text |Cite
|
Sign up to set email alerts
|

The Human in Vitro Anti‐type 4 Pneumococcal Polysaccharide Antibody Response is Regulated by Suppressor T Cells

Abstract: In order to study the regulation of the human B-cell response to T-cell independent type 2 (TI-2) antigens, we analysed the role of T cells in the in vitro antibody response to type 4 pneumococcal polysaccharide (PS4). We found that T cells can positively regulate the in vitro antibody response to PS4 when they are added into an in vitro B-cell culture system. In addition we demonstrated that T cells exert a negatively regulating activity. We found that T cells, when cultured for 24 h in the presence of high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…They stated that "usually the effects produced by Ts and Ta are counterbalanced: this is why the Ab response to SSS-III is similar in magnitude in thymus-bearing and athymic mice and why Ts and Ta have escaped detection for so many years." The existence of stimulatory and inhibitory T cells has been confirmed by other groups (23,24) and, more recently, we further substantiated that CD4 ϩ T lymphocytes exert stimulatory, and CD8 ϩ T lymphocytes exert inhibitory, effects, and that these effects depended on the CD40L-CD40 interaction (9,10). In the present manuscript, we demonstrate that CD4 ϩ T cells expressing CD40L help the IgM Ab response to soluble pneumococcal caps-PS via an intermediate cell type.…”
Section: Discussionsupporting
confidence: 70%
“…They stated that "usually the effects produced by Ts and Ta are counterbalanced: this is why the Ab response to SSS-III is similar in magnitude in thymus-bearing and athymic mice and why Ts and Ta have escaped detection for so many years." The existence of stimulatory and inhibitory T cells has been confirmed by other groups (23,24) and, more recently, we further substantiated that CD4 ϩ T lymphocytes exert stimulatory, and CD8 ϩ T lymphocytes exert inhibitory, effects, and that these effects depended on the CD40L-CD40 interaction (9,10). In the present manuscript, we demonstrate that CD4 ϩ T cells expressing CD40L help the IgM Ab response to soluble pneumococcal caps-PS via an intermediate cell type.…”
Section: Discussionsupporting
confidence: 70%
“…Up to now, only scarce evidence for a possible role of T lymphocytes and the CD40-CD40L interaction in the human immune response to caps-PS is available. Griffioen et al [11,20] provided evidence that CD4 + T lymphocytes stimulate and CD8 + T lymphocytes inhibit the human immune response to caps-PS in vitro. Leiva et al [12] showed induction of CD40L on T lymphocytes by stimulation with TI-2 antigens, which suggested that the CD40-CD40L interaction could play a role in the human immune response to caps-PS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that typical TI-2 antigens can activate murine T cells in an antigen-specific manner and induce them to provide help to B cells for the production of IgG antibody responses (33). Griffioen et a1 (34) suggest that the ongoing antibody responses to some TI-2 antigens, such as pneumococcal capsular polysaccharide, are under the strong influence of regulatory T cells that can exert either an amplifying effect or a suppressive effect. This antibody response to TI-2 antigens is regulated by an antigenspecific suppressor function that is MHC restricted.…”
Section: Discussionmentioning
confidence: 99%